The Possibilities of Dynamic Phenomena Calculation in the Penstock of Hydropower Plant via Different Methods - Hlbočan Peter; Ďurčanský Peter; Csuka Zoltán; Kiš Roman; Kolková Zuzana (MATEC Web of Conferences, 2022)
When designing a hydropower plant with a long pressure penstock, special attention must be paid to the pressure conditions in the penstock, especially during emergency flow shutdown. In this paper, the main principles of the calculation of static pressure rise in the pressure pipeline during rapid flow shutdown are presented. The results obtained by analytical methods (calculation of direct and indirect water hammer) and numerical methods (mathematical modelling in Matlab software environment) are compared on specific examples. The influence of some input parameters of the numerical model on the results of the numerical calculation is analysed separately.